(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
Uzbekistan has become an essential part of the South Korean labor market under the Employment Permit System (EPS). From early diplomatic ties and internships, worker mobility between South Korea and Uzbekistan has been increasing day by day since the 1990s. Uzbek workers impacted economically and socially in manufacturing, agriculture, and other important industries, as well as governmental agreements have influenced legal migration patterns. However, there were numerous difficulties they encountered, such as unstable employment, legal limitations, and the COVID-19 pandemic’s effects. Notwithstanding these challenges, Uzbek immigrants have helped to sustain South Korea’s output in trying times. Looking to the future, this article examines opportunities for creating a fairer and more sustainable migration system through improved professional preparation, support, and policy refinement. Beyond economic aspects, this labor migration serves to strengthen cultural connections and mutual trust between the two countries.